The Effect of Tax Planning and Deferred Tax Expense on Earnings Management (Empirical Study on Financial Service Companies Listed on the Indonesia Stock Exchange for the 2020–2024 Period) - Septyani, Annisa Putri; Hartono, Hartono (Jurnal Ekonomi, 2025)
This study investigates the effect of tax planning and deferred tax expense on earnings management in financial service companies listed on the Indonesia Stock Exchange during a multi-year period. The research adopts a quantitative approach using panel data regression analysis with the fixed effect model, based on secondary data obtained from publicly available financial statements. The findings reveal that tax planning does not have a significant impact on earnings management, while deferred tax expense shows a significant negative relationship with earnings management. Simultaneously, both variables significantly influence earnings management practices. These results suggest that deferred tax expense plays a more critical role than tax planning in shaping financial reporting behavior. The study contributes to the existing literature by offering empirical evidence within the context of financial service firms in a developing country and provides insights for stakeholders to better interpret deferred tax figures in relation to potential earnings manipulation.